OPTIMALISASI METERAN AIR DIGITAL MENGGUNAKAN SISTEM INTERNET of THINGS DI PDAM TIRTASILAUPIASA - Bagus Ardiansyah Putra; Herman Saputra; Mhd Ihsan (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2023)
Water is an essential compound for all forms of life on earth. Therefore, several companies take advantage of this to distribute water. One of them is the TIRTASILAUPIASA PDAM company which distributes drinking water to customers' homes. To calculate the customer's total water use, the PDAM only needs to record it through the water meter that was previously installed at the customer's house. However, because the water meter is still manual, some deficiencies such as the water meter is dewy, the door of the customer's house is locked, making it difficult for the water meter reader to see and record the customer's water usage. Misunderstandings with customers often occur due to usage that does not match the amount to be paid. And because of this, PDAM TIRTASILAUPIASA has lost its good image. The solution to this problem is to replace manual water meters with digital water meters using the Internet of Things system. Where, this digital water meter can see the customer's water usage without the need to come to the customer's house. PDAM can view and monitor customers' water usage through a website. In this way, misunderstandings with customers will not occur because the PDAM has obtained accurate data.